“Tired, Overwhelmed, Frustrated”: Emotional Challenges of Primary English Teachers During the Pandemic: Case Study in San Carlos, Costa Rica - López-Estrada, Patricia (2024)
Introduction. COVID-19’s health crisis put a hold on all educational processes worldwide. This was not the exception for Costa Rica at the Ministry of Education. In March 2020, it was proposed that distance education was going to be put into practice. Purpose. This paper focuses on the feelings the participants communicated during the study. This was part of a principal investigation that used a case study methodology based on inductive qualitative research. It had the purpose of describing the perceptions of four English primary school teachers from the Dirección Regional de Educación San Carlos (San Carlos Regional Education Office) regarding distance education during the sanitary emergency of COVID-19. Methodology. Data were collected through in-depth interviews, lesson plans, and video recordings of pedagogical mediation and professional contexts. The data were analyzed using semantic categories from content analysis (Hatch, 2002) and the Web Qualitative Data Analysis (webQDA) software (Costa et al., 2019). Results. Results suggest that teachers reported experiencing a range of emotions before and during the pandemic, with the majority being negative in nature. Among the most notable were uncertainty, stress, confusion, overwork, a sense of difficulty, sadness, and worry. Other feelings included discrimination, impotence, and disrespect towards the teachers and the families’ specific contexts. This study presents the teachers from their human dimension as professionals who endured the pandemic within their own educational contexts. The study also shows the importance of effective communication and taking into consideration psychological support to strengthen the emotional integrity of the teachers.